Corneal Decompensation after Selective Laser Trabeculoplasty. (30th June 2014) - Ozkok, Ahmet; Tamcelik, Nevbahar; Ucar Comlekoglu, Didar; Iskeleli, Guzin
Abstract : A 64-year-old Caucasian man referred for decreased vision after selective laser trabeculoplasty (SLT). Slit lamp examination revealed diffuse corneal edema. Despite intensive topical treatment including steroids, corneal edema did not resolve; on the contrary, it advanced to bullous keratopathy. Corneal edema after SLT is an exceptionally rare complication and in all of the previous reports edema resolved with medical treatment. To the best of our knowledge, this is the first report presenting persistent corneal edema after SLT.